Toward 1984 : The Future of Appalachia - Roseberry, Helen (Appalachian State University, 1975)
Though titled the Proceedings of the 1st Annual Appalachian Studies Conference, this volume contains the speeches and papers of the Southern Appalachian Regional Conference held May 13-16, 1974 at the Center for Continuing Education at Appalachian State University. Governor James E. Holshouser, Jr. of North Carolina; John B. Howard, American Petroleum Institute; and Cratis Williams, Acting Vice Chancellor for Academic Affairs, Appalachian State University each spoke at the opening banquet. The primary topics of the conference were energy, land use, and the human spirit. The conference was sponsored by the Appalachian Consortium and was a part of Project Open of the United States Office of Education.
English
Keywords: Regional studies; Social Science; Regional Studies